Flow pattern induced by the plane piston moving in a non-ideal gas with weak gravitational field - Singh L.P.; Ram S.D.; Singh D.B. (My University, 2025)
A systematic perturbation scheme is used to analyze the flow pattern induced by the motion of a plane piston moving with constant velocity in a non-ideal gas with weak gravitational field. The flow variables are expanded as a series of small parameter , which is the ratio of the typical escape velocity to the plasma velocity. The zeroth order solution gives the uniform flow which is influenced by the parameter of non-idealness without gravity. The first order relationships show the influence of non-idealness of the gas as well as the applied gravity on the flow field. Distribution of the flow variables has been presented graphically for various values of parameter of non-idealness. The structure of the shock front in case of small perturbation theory is also discussed. © 2011 Ain Shams University. Production and hosting by Elsevier B.V. All rights reserved.